Complete tubular duplication of colon in an adult: a rare cause of colovaginal fistula - Jung, Hae Il (Ann Surg Treat Res, 2016)
Alimentary tract duplications are uncommon congenital anomalies that usually present during the first decade of life. Complete duplication of the colon in adults is very rare and difficult to diagnose preoperatively. We report a case of a 40-year-old female with complete tubular duplication which was initially misdiagnosed as a salpingeal abscess due to colovaginal fistula.